Vasal Irrigation With Sterile Water and Saline Solution for Acceleration of Postvasectomy Azoospermia - Roshani, Ali; Falahatkar, Siavash; Khosropanah, Iradj; Asghari Golbaghi, Mohamad Reza; Kiani, Seyed Amir; Akbarpour, Marzieh (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: Vasectomy is the safest and most reliable method of all the contraception methods, but azoospermia is not achieved immediately by this method. We decided to determine whether irrigation of the vas deferens with sterile water or hypertonic saline solution irrigation during vasectomy would reduce the time needed to obtain azoospermia. Materials and Methods: A total of 126 fertile men presented for vasectomy were divided in 3 groups. No-scalpel vasectomy was done for all of the participants and irrigation of the vas deferens was carried out during the procedure in 2 groups with either sterile water or hypertonic saline solution (9 g/L sodium chloride solution). Forty-two participants underwent vasectomy without irrigation. Semen analysis was performed at 4, 8, 12, and 16 weeks after vasectomy. Results: Azoospermia was achieved in all of the men with sterile water after 12 weeks, while at the end of the study (16 weeks) it was achieved in 37 (88.1%) of those with saline solution and in 11 (26.2%) of those without irrigation. There were significant differences in the rates of azoospermia between the participant with sterile water and saline solution at 8 weeks (38.1% versus zero; P < .001), 12 weeks (100% versus 30.9%; P < .001), and 16 weeks (100% versus 88.1%; P = .02). No pregnancy developed during the follow-up and no complication was reported. Conclusion: Vasal irrigation with sterile water and hypertonic saline solution during vasectomy were effective in removing sperm from the distal vas and increasing the rate at which men achieved azoospermia. Sterile water was a promising option with no complications.